Sexuality of female royals in renaissance plays: Duchess of Malfi, Gertrude and Cleopatra - Prioti, Ishrat Jahan (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2017.